Pengaruh Puasa Vikâla Bhojana terhadap Kadar Trigliserida dan Gula Darah pada Komunitas Bhikkhu Theravâda - Fredy Fredy; Budi Utomo; Khie Khiong (Majalah Kedokteran Indonesia, 2019)
Introduction: Heart disease and stroke are the top two causes of death in the world that are associated with high cholesterol and blood glucose level due to the wrong diet. Objective: The objective of this study is to prove the effect of vikâla bhojana (Buddhist fasting) on triglyceride and fasting plasma glucose levels on Theravâda monks community in Medan city. Method: The research method used is quasi experimental design with non equivalent control group. A purposive sampling technique with inclusion criteria has been applied to respondents, which consisted of 18 monks and 18 laypeople. Anthropometric measurements and biochemical blood analysis are used to collect data. Statistical analysis is performed by using a single sample t-test, unpaired t-test, and Pearson Product Moment. Result: The research statistic shows the value of p=0,006 (p < 0,05), indicating there is a significant difference between the mean of triglyceride and fasting plasma glucose level among groups. Conclusion: Although the main purpose of vikâla bhojana (Buddhist fasting) is to attain self-control, vikâla bhojana (Buddhist fasting) can reduce triglyceride and fasting plasma glucose level.